WOMEN AND POLITICAL PARTIES: A GENDER SOCIOLOGICAL PERSPECTIVE - Abdullah Ismail; Muhammad Haji Noh; Amrul Djana (International Journal of Multidisciplinary Reseach, 2026)
Women's participation in political parties is an important indicator of democratic quality. Nevertheless, women continue to encounter structural, cultural, and institutional barriers that limit their full participation in political processes. Drawing upon a gender sociology perspective, this paper examines the factors contributing to the persistent underrepresentation of women in politics, particularly in Indonesia. This study employs a qualitative approach based on a literature review to explore the interplay between gender relations, patriarchal culture, and the internal dynamics of political parties. The analysis demonstrates that increasing women's political representation requires not only affirmative policies but also broader social transformation through changes in gender norms and the strengthening of women's political capacity.